Associação entre Helicobacter pylori e polimorfismos em genes de interleucinas no câncer gástrico - Costa, Débora Menezes da (2012)
The carcinogenic role of Helicobacter pylori is related to its ability to promote inflammation and, consequently, DNA methylation, epigenetic trait often associated with gastric carcinogenesis. In turn, the inflammation can be modulated by the presence of polymorphisms in some interleukin genes, as well as the bacterial genotype. The objectives of this study were: a) link the genotypic profile of H. pylori virulence (cagA, cagE, vacA and virB11 genes) and genotypic profile of pro-inflammatory interleukins polymorphisms, IL1β -511 C/T, IL1RN, IL6 -174 G/C and TNF-308 G/A with gene promoter methylation of CDKN2A, MLH1, and COX-2 b) verify the association of polymorphisms of IL6 -174 G/C and TNF -308 G/A with bacterial genotype in the gastric cancer development, considering the clinical and pathological aspects. For this, DNA was extracted from 125 tumor samples, collected from patients who underwent gastrectomy at hospitals in Fortaleza – Ceará – Brazil. Polymorphisms genotyping were identified by PCR-RFLP and methylation analysis by MS-PCR. Virulence genes of H. pylori were analyzed by PCR. In some analyzes, the bacterial genotypes were grouped according to the alleles of vacA and integrity of cag-PAI. In this study, we observed that in cardia tumors the methylation of COX-2 promoter region was associated with IL1RN*2 allele (p=0.015), and genotype IL-1B -511T+IL1RN*2 was important to methylation of this gene (p=0.013), especially in the presence of H. pylori cagA+strains (p=0.020) and vacA s1 (p=0.032). The genotype combination IL6 CC+TNFGG seems to be involved in non-methylation of promoters of genes CDKN2A (p=0.046) and MLH1 (p=0.031), even in the presence of infection by strain H. pylori cagA+. Considering the clinical and pathological aspects, a positive correlation was found between males and patients aged >65 years (r=0.198, p=0.037), in which this gender was predominant (77.5%, p=0.022) . In addition, positive correlation was found between female and patients aged 55-64 years (r=+0.217, p=0.021). Regarding the histologic subtype, we found that diffuse tumors were correlated with younger patients (15-44 years, r=+0.207, p=0.033), while the intestinal subtype, with the older patients (>65 years, r=+ 0.296, p=0.017). Tumors of the diffuse subtype were correlated with female gender and those of the intestinal subtype, with males (r=+0.226, p=0.019). Regarding polymorphisms of interleukins, the C allele of IL6 polymorphism -174G/C was negatively correlated with the younger group (r=-0.193, p=0.041), and the patients with CC genotype of IL6 was associated with infection by virulent strains (group 1c) (r=+0.225, p=0.017), whereas patients with the genotype IL6 -174 GC, with virulent strains (group 1c) (r=-0.215, p=0.023) and less virulent (group 2c) (r=+0.204, p=0.031). Our findings contribute to the establishment of a genotypic profile involved in methylation of some genes in which patients with genotype more inflammatory and infected with strains of H. pylori more virulent are associated with a higher rate of methylation of some genes involved in gastric carcinogenesis and may also vary according to location and tumor subtype. This study thus provides an important contribution with regard to the association of the strain of H. pylori polymorphisms interleukins, in which most virulent strains appear to be related to infection of patients with inflammatory genotypes less, and the converse is also true.